1996
DOI: 10.1002/jbmr.5650110515
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastic superoxide production and bone resorption: Stimulation and inhibition by modulators of NADPH oxidase

Abstract: Production of superoxide radicals by osteoclasts is necessary for normal bone degradation. White blood cell superoxide, needed for bacterial killing, is produced by activated NADPH oxidase. Since osteoclasts and white blood cells share a common hematopoietic origin, we initiated experiments to test the hypothesis that superoxide radicals at the osteoclast-bone interface are produced by NADPH oxidase. Diphenyl iodonium (IDP), an inhibitor of NADPH oxidase, blocked superoxide generation and decreased osteoclasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Subsequent studies from other groups also found that superoxide production was present within the osteoclast and suggested that it may be derived from nicotinamide adenine dinucleotide phosphate (NADPH) oxidase localized to the bone-osteoclast interface within the osteoclast ruffled border [14][15][16]. Further evidence for the involvement of NADPH oxidase was found when addition of a specific inhibitor of NADPH oxidase, diphenylene iodonium (DPI), resulted in a reduction in superoxide production and bone resorption [17,18]. Other studies, however, indicated that rather than superoxide, H 2 O 2 was the primary ROS responsible for promoting osteoclast formation and activity [8,[19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…Subsequent studies from other groups also found that superoxide production was present within the osteoclast and suggested that it may be derived from nicotinamide adenine dinucleotide phosphate (NADPH) oxidase localized to the bone-osteoclast interface within the osteoclast ruffled border [14][15][16]. Further evidence for the involvement of NADPH oxidase was found when addition of a specific inhibitor of NADPH oxidase, diphenylene iodonium (DPI), resulted in a reduction in superoxide production and bone resorption [17,18]. Other studies, however, indicated that rather than superoxide, H 2 O 2 was the primary ROS responsible for promoting osteoclast formation and activity [8,[19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…The level of Nox2 expressed in murine osteoclasts is almost double of that in phagocytes, suggesting that the NADPH oxidase complex is highly expressed in osteoclasts [72] , which may explain the higher levels of O 2 -ؒ generated by these cells [68,84,85] . O 2 -ؒ has been detected at the ruffled border of osteoclasts, which suggests that ROS are produced at sites of resorption and may participate in matrix degradation.…”
Section: Ros Production and Nadph Oxidase Expression In Multinucleatementioning
confidence: 93%
“…Based on their cellular origin, it is not surprising that the various types of multinucleated giant cells have been shown to generate ROS, as ROS production is one of the hallmarks of all professional phagocytes, including neutrophils and monocyte/macrophages [reviewed in 66 ]. Among the multinucleated giant cells known to generate ROS are osteoclasts [67,68] and multinucleated giant cells of noninfectious and infectious granulomas [69][70][71] . Note, however, that multinucleated giant cells generally exhibit an enhanced ROS-generating capacity (20-to 30-fold) compared with unfused macrophages [69] .…”
Section: Ros Production and Nadph Oxidase Expression In Multinucleatementioning
confidence: 99%
“…Theoretically, copper should impact bone since the copper enzyme lysyl oxidase crosslinks collagen, which contributes to bone strength [1,11]. Also, Cu-Zn SOD eliminates the oxidant superoxide, which promotes bone breakdown [13].…”
Section: Introductionmentioning
confidence: 99%